The problematic of concepts among the critical speech in modern Arab thought : Mohammed Abed Al Jabri - George Tarabishi - gemiti, khadidja (Journal of Social Sciences and Humanities, 2020)
The study aims at examine the problem of concepts based on the critical discourse between the thinker Muhammad Abed al-Jabiri and the thinker George Tarabishi as a matter raised in contemporary Arab thought, with a huge critical series , which is characterized by the criticism of the Arab mind of al-Jabiri, debating with a series of criticizing the criticism of the Arab mind of Tarabishi, and it adopts as a whole the most important intellectual projects and issues , Which was presented by Tarabishi with a conceptual critical epistemological contemporary approach. The purpose of it is to call for the consideration of the formation of mind and its structure and the revolution on the tradition that restricted this Arab mind and causes him a big crisis fora long period of time on the one hand and the call for copying and quoting from the western one from the other Hand which calls for scrutinizing with a critical comparative approach, depending on the intellectual references that were established by Jabiri philosophy.Therefore, the subject of our study revolves around the project presented by Tarabishi as a critical project to Al Jabiri in terms of concept and the formation of concept and the call for the concept to be redefined from an epistemological point of view in accordance with the requirements of the Arab mind, including the project of criticizing the Arab mind, reading in the heritage and splitting the mind in addition to other concepts. Keywords: The Concepts, the discourse ,the Critical discourse, Contemporary Arab thought, Renewal, Criticism of concepts.